Goal-Oriented Learning in Private Music Education: Case Study on Piano, Keyboard, and Drums - Sembiring, Piter; Maulana, Marsel Ridky; Nurfalah, Asep Rizwan; Muqri, Al (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to examine the effectiveness of a goal-oriented approach in private music education, particularly in mastering keyboard, piano, and drum instruments. The research focuses on how structured learning objectives influence students motivation, engagement, and technical proficiency.Method – This qualitative study employs a case study methodology, incorporating in-depth interviews, direct observations, and document analysis. Four students from different age groups participated in private music lessons at their homes, following a customized curriculum tailored to their individual learning needs. Findings – The results indicate that a goal-oriented learning approach significantly enhances students' understanding of basic notation, instrumental techniques, and overall motivation. In keyboard lessons, students demonstrated improved finger positioning and notation reading skills. Piano students mastered chord inversions and harmonic applications, while drum students gained proficiency in reading and executing rhythmic notations. Despite its effectiveness, the approach may limit creativity if it excessively prioritizes structured objectives over exploratory learning. Research Implications – This study highlights the importance of structured learning in private music education while acknowledging its potential constraints. Future research should explore ways to balance goal-oriented instruction with creative exploration to optimize learning outcomes.